2021
DOI: 10.46303/jcsr.2021.4
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Online Teaching and Digital Learning: Lessons Learned in the Time of Pandemic and Beyond

Abstract: When the COVID-19 pandemic swept across the world in 2020 and into 2021, the entire system of education faced the most challenging task to provide education to students using virtual instruction. Within the United States specifically, the pandemic transformed teaching. Teachers were and have continued to be compelled to learn digital technology and integrate varied digital tools into their instruction. As guest editors, Eric and I had the opportunity to reflect on the many instructional challenges and valuable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The proposition about the "unity of both nature and politics", reflected, in particular, in the philosophy of Bruno Latour (Latour et al, 2004;Latour et al, 2005;Kulikova, 2021), allows using a variety of views on the essence and nature of resilience as characterizing one and the same complexly organized object in its various manifestations. When regarding these positions, the results of resilience studies can be transferred from various fields of knowledge, including natural sciences, and used to answer the research question posed (Evans-Amalu and Claravall, 2021;Tarman and Kilinc, 2022;Kilinc and Tarman, 2022). If phenomena have the same name, they must be essentially similar, regardless of their nature.…”
Section: Methodsmentioning
confidence: 99%
“…The proposition about the "unity of both nature and politics", reflected, in particular, in the philosophy of Bruno Latour (Latour et al, 2004;Latour et al, 2005;Kulikova, 2021), allows using a variety of views on the essence and nature of resilience as characterizing one and the same complexly organized object in its various manifestations. When regarding these positions, the results of resilience studies can be transferred from various fields of knowledge, including natural sciences, and used to answer the research question posed (Evans-Amalu and Claravall, 2021;Tarman and Kilinc, 2022;Kilinc and Tarman, 2022). If phenomena have the same name, they must be essentially similar, regardless of their nature.…”
Section: Methodsmentioning
confidence: 99%
“…If students do not receive adequate support in online learning, they are less likely to be able to continue their learning [20]. Researchers have called for more investigation into the support for inclusive online learning [21,22]. Therefore, it is critical to gain a better understanding of the support or lack of support that university students experienced in online learning during the COVID-19 pandemic.…”
Section: Literature Review 21 Support For Inclusive Online Learning I...mentioning
confidence: 99%
“…The lack of quality internet connection affected most of the students to participate in real-time online classes, and to complete asynchronous learning tasks at their own pace during the pandemic [22]. It was challenging for them to interact with their teachers and peers without a stable internet connection.…”
Section: Autonomy Support: Enhancing Accessibility To Online Learningmentioning
confidence: 99%
“…After identifying the key performance indicators of a modern university, a decision is made to adjust its strategy. As the literature review has shown, the main directions of development of modern universities are associated with the expansion of the use of digital technologies (Bolgova et al, 2020;Evans-Amalu and Claravall, 2021;Williams et al, 2021;Demichev, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%